How and what marketing algorithms think - Brognara, Roberto (Newcastle upon Tyne : Cambridge Scholars Publishing, 2023)
This book argues that the apparent omnipotence of algorithms today is not what it seems, particularly, in marketing, where they actually offer less than they could. Considering the reasons behind this, it also notes that Big Data has relaunched a kind of data glorification and automated procedures that, culturally, marketing has already recognized and overcome at least once.This first generation of "programmatic marketing", which the giants of the digital economy launched 15 years ago and consolidated worldwide, can be significantly improved, with corresponding business results as well, but, first, as this book shows, we need to know which strategic and cultural boundaries impact Big Data.
Intro -- Table of Contents -- Preface -- Introduction -- 1. -- 2. -- 3. -- 4. -- 5. -- Bibliography.
Description based on online resource; title from digital title page (viewed on December 05, 2022).
eBooks on EBSCOhost
Keywords: Algorithms; Marketing -- Data processing; Big data; Algorithmes; Marketing -- Informatique; Données volumineuses; algorithms; Algorithms; Big data; Marketing -- Data processing